PEMAHAMAN MASYARAKAT TENTANG STRATEGI PERWUJUDAN GOOD GOVERNANCE PADA PEMERINTAH KECAMATAN BANCAK KABUPATEN SEMARANG: SUATU KAJIAN ANTROPOLOGIS (Solidarity: Journal of Education, Society and Culture, 2012)
This article examines the emic understanding of the society on good governance in the system of government in the Kecamatan Bancak. People’s understanding of good governance based on everyday experience and the interests of administrative arrangements. The process of administrative services in the Kecamatan Bancak not entirely based on the aspects of good governance is conceptualized PP no. 10/2000 about training of civil servants. The strategy used to cultivate good governance is the ”social capital”. Based on the research results can be concluded that the public understand the good governance is resik (saka dhuwit), gampang, murah, cepet lan cedhak karo wong cilik. Kecamatan Bancak government has not fully run aspects of good governance, but the people accept and believe that the government has met the expectations of society as a Good governance. Public acceptance based on the close relationship between government and social kinship with the society.